Digital Manipulation: Self-Presentation in the Film The Tinder Swindler - Fernandez, Maria Angela; Rahmanto, Andre Noevi; Pawito (UIR Press, 2025)
The development of digital technology, including social media, has emerged as a means of communicating with other people, one of which is the dating application called Tinder. Socializing, doing work, dating, and sharing life stories on social media are examples of daily activities carried out by people around the world. The focus of this research is on identity manipulation techniques which are studied using self-presentation strategy theory by Erving Goffman. This study describes how the main character uses digital platforms to manipulate using the Tinder application, as documented in the documentary film